ON THE SOLUTIONS OF A HYPERBOLIC NONLINEAR SYSTEM WITH BOUNDARY DIFFERENTIAL INCLUSION AND NONLINEAR SECOND ORDER DAMPING OVER THE BOUNDARY - Perez Salvatierra, Alfonso (2008)
In this paper we study the existence of generalized solutions for a hyperbolic nonlinear system with a discontinuous multi-valued term and nonlinear second-order damping terms on the boundary.